Tradisi Bulan Suro dalam Cerpen 'Merayakan Cinta' Karya Rehilia Tiffany: Sebuah Analisis Sosial Kajian Teori Lucien Goldmann - Khairunnisa, Nia; Cantika Mawarni; Nursalassaty; Rehilia Tiffany; Andina Hadawiyah (Indo-MathEdu Intellectuals Journal, 2025)
The modernization that occurred is reflected in the short story 'Celebrating Love' by Rehilia Tiffany. This short story contains social and cultural values of the community, which is relevant today. This research aims to uncover the social value in short stories, including human aspects, collective subjects, and the author's worldview based on Lucien Goldmann's theory. The method used is qualitative descriptive, including the stage of literature study, data analysis, and validity test. Data was collected from short story texts, information sources such as books and scientific articles, then analyzed while performing open coding, axial coding, and display coding. The results are (1) aspects of humanitarian facts in the form of conflicts between modern values held by Laras and cultural norms embraced by local communities, (2) aspect of collective subject, namely from the community's belief that violating the taboo of the month of Suro can bring bad luck, reflecting how myths and collective beliefs remain influential in people's lives which act as agents to pressure individuals to obey traditions, and (3) the author's worldview is reflected in Hisyam and Laras  actions, who choose to postpone their marriage and celebrate their love simply while respecting traditions.